Promoting the economic reintegration of returnees through vocational training: lessons from Liberia. Issue 8 (17th November 2018) - Omata, Naohiko; Takahashi, Noriko
ABSTRACT: Through a follow-up study, this article explores the role of vocational training programmes in promoting the economic reintegration of repatriated refugees in Liberia. In 2014, we conducted an initial study on livelihood outcomes of vocational training programmes provided by the United Nations Industrial Development Organization for Liberian returnees. By tracing the trained returnees two years after the completion of training, the article investigates the employment and economic conditions of these former beneficiaries and aims to provide valuable insights into the potential and limitations of vocational training programmes in relation to refugees' economic reintegration post-repatriation.